POTENSI DAN KONTRIBUSI SUMBER DAYA MANUSIA TERHADAP PENINGKATAN PENDAPATAN KELUARGA - Kiagus Muhammad Zain Basriwijaya, Hamdi Sari Maryoni (Fakultas Ekonomi Universitas Pasir Pengaraian, 2017)
The important role of human resources in improving the economy. Gender or gender status greatly affects income generation in the family. Women as a leader of the family has a very important role. Both in managing the family and can play a role as head seekers family to earn a living. Living. In this study the occupations occupied by women are farmers. Data collection techniques used survey and interview methods. Data analysis technique used is quantitative analysis. The results of research on the role of women to the family income in the village of Pasir Utama Rambah Hilir sub-district Rokan Hulu District contributed income of Rp. 10.977.559 / year and contributed 31.98% of total family income.